The Effectiveness of Flipped Classroom Teaching Mode In Colleges and Universities - Li, Jing (Journal of Theory and Practice of Social Science, 2024)
Under the background of the rapid development of today's society, higher requirements are put forward for the teaching model. As a product of education reform, flipped classroom has gained rapid popularity and development both at home and abroad. This paper mainly analyzes from the aspects of improving teachers' information literacy, stimulating students' enthusiasm for independent learning, and effectively using information technology, and discusses how to improve the effectiveness of flipped classroom teaching mode in colleges and universities, hoping to provide some experience for educators.